2017
DOI: 10.1089/ars.2016.6851
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of the Mitochondrial Protein Fus1 in Protection from Premature Hearing LossviaRegulation of Oxidative Stress and Nutrient and Energy Sensing Pathways in the Inner Ear

Abstract: Since chronic mitochondrial dysfunction is common in many patients, it could lead to developing hearing loss that can be alleviated/rescued by AO treatment. Our study creates a framework for clinical trials and introduces the Fus1 KO model as a powerful platform for developing novel therapeutic strategies to prevent/delay hearing loss associated with mitochondrial dysfunction. Antioxid. Redox Signal. 27, 489-509.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 76 publications
2
52
0
Order By: Relevance
“…The analysis was performed off-line in BioSig (BioSig Technologies) on traces with visible peaks by setting cursors at the maxima and minima of the peaks. Latency was defined as the time from the onset of the stimulus to the peak, while amplitude was measured by taking the mean of the ⌬V of the positive and negative deflections of the ABR wave (Tan et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was performed off-line in BioSig (BioSig Technologies) on traces with visible peaks by setting cursors at the maxima and minima of the peaks. Latency was defined as the time from the onset of the stimulus to the peak, while amplitude was measured by taking the mean of the ⌬V of the positive and negative deflections of the ABR wave (Tan et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Besides the data presented in this manuscript that we discuss below, we recently showed that Fus1 KO mice prematurely and progressively lose their hearing [63]. Early deterioration of hearing parameters measured in young adult Fus1 KO mice via Auditory Brainstem Response (ABR) and molecular perturbations in their cochleae were similar to the aging-related processes that occur in people of 70 years of age and older.…”
Section: Discussionmentioning
confidence: 76%
“…ABR experiments in this study were conducted using the same apparatus (TDT3 system with a FF1 speaker, Tucker-Davis Technologies) and procedures described in (Tan et al, 2017, El-Hassar et al, 2019. Auditory thresholds were determined based on waves I and II (see also Figure 5A).…”
Section: Auditory Brainstem Response (Abr)mentioning
confidence: 99%